Nanocosméticos: uma breve revisão - Santos, Matheus Freitas dos (Universidade Federal de São Carlos, 2024)
Nanoscience has been driving a rapid revolution in the cosmetics industry for years. This phenomenon is evidenced by the widespread presence of nanotechnology in various products for even more diversified applications, catering to skin, hair, nail, dental, and lip care. The benefits of this technology represent an innovative solution to overcome the limitations of conventional cosmetic products. A variety of nanomaterials such as liposomes, nanoemulsions, polymeric nanoparticles, lipid-based nanoparticles, metallic nanoparticles, and carbon-based nanoparticles, among others, are employed in the differentiated and revolutionary formulation of cosmetic products. These materials offer unique properties due to the high ratio of surface area to volume. This results in a greater capacity to load active compounds, improved absorption, enhanced cosmetic efficacy, and therapeutic benefits, depending on the material used. However, the use of nanocosmetics is not without challenges. Concerns about the potential toxicity of these products when exposed to humans through unintentional inhalation, ingestion, and skin penetration are critical issues. The dynamics of the cosmetic industry, aiming to meet the needs and trends of consumers, lead to the creation of new nanomaterials. This, in turn, requires a response from regulatory bodies, which must establish laws and guidelines to assess the reliability of these innovations and ensure consumer safety. In summary, the integration of nanotechnology into the cosmetic industry is a significant evolution, offering aesthetic and therapeutic benefits, but it requires a cautious approach to ensure the safety of these innovative products.
Nanocosmetics - a review
Keywords: Produtos cosméticos; Nanotecnologia; Nanopartículas; Toxicidade; CIENCIAS EXATAS E DA TERRA::QUIMICA